Evaluasi Kinerja Jalan Berdasarkan Variasi Waktu - Maulia Rahmad; Meliyana Meliyana; Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Sultan Iskandar Muda Airport Road, is the main access from Sultan Iskandar Muda Airport to the city and vice versa, because of these factors, it is estimated that this region has a high position and access to traffic in the future. The purpose of this study is to review the performance of roads on the Sultan Iskandar Muda Airport road based on time variations. The road section reviewed is 1 km with a width of 3.25 m. This road performance review was conducted using the 1997 MKJI reference. Traffic volume data, side barriers, travel speed and road geometry were obtained directly from field surveys for seven days of observation (06.30-08.30; 11.30-13.30; and 17.00-19.00), while Secondary data in the form of population and location research data obtained from relevant agencies. The analysis shows that the highest traffic volume occurs on Monday at 07:30 to 08:30 which is 1043 pcu / hour with a degree of saturation (DS) of 0.339 and the lowest traffic volume occurs on Saturday 06.30-07.30 which is 962 pcu / hour with a degree of saturation of 0.093. The value of the degree of saturation in the highest traffic volume (Monday), which is 0.339, is still far from the limit value of the saturation degree set by MKJI 1997, which is <0.75. This proves that the Sultan Iskandar Muda Airport road performance is still very good.